Acute toxoplasmosis-etiological factor for development of Hodgkin's lymphoma? - Snopkova, Svatava; Pohanka, Miroslav; Polak, Pavel; Havlickova, Katerina; Jarkovsky, Jiři; Moulis, Mojmir; Stroblova, Hana; Husa, Petr (Scandinavian journal of infectious diseases, 2013)
The case of an HIV-positive man treated for acute toxoplasmosis with no traces of malignancy is reported. A second lymph node extirpation was performed after 5 months, which identified the presence of Hodgkin and Reed-Sternberg (HRS) cells. This case suggests that toxoplasmosis may cause changes in the regulation of surrounding cells and induce neoplastic proliferation.
Keywords: Toxoplasmosis; buňky Reedové-Sternberga; toxoplazmóza; Hodgkinova nemoc; mužské pohlaví; Reed-Sternberg Cells; HIV infekce; dospělí; Humans; Adult; HIV Infections; Hodgkin Disease; lidé; Male